Architecture- and Composition-Controlled Self-Assembly of Block Copolymers and Binary Mixtures With Crosslinkable Components: Chain Exchange Between Block Copolymer Nanoparticles - Li, Panpan; Davis, Jesse L.; Mays, Jimmy W.; Wang, Xu; Kilbey, S. Michael (Frontiers in Chemistry, 2022)
Chain exchange behaviors in self-assembled block copolymer (BCP) nanoparticles (NPs) at room temperature are investigated through observations of structural differences between parent and binary systems of BCP NPs with and without crosslinked domains. Pairs of linear diblock or triblock, and branched star-like copolymers that self-assemble in a PVP-selective mixed solvent (methanol/THF at 3:1 v/v) into BCP NPs with definite differences in size and self-assembled morphology are combined by diverse mixing protocols and at different crosslinking densities to reveal the impact of chain exchange between BCP NPs. Clear structural evolution is observed by dynamic light scattering and AFM and TEM imaging, especially in a blend of triblock+star copolymer BCP NPs where the spherical and vesicular structures of the parent BCPs, respectively, give rise to a system of spherical nanoassemblies. The changes are ascribed to the chain motion inherent in the dynamic equilibrium, which drives the system to a new structure, even at room temperature. Chemical crosslinking of PVP corona blocks suppresses chain exchange between the BCP NPs and freezes the nanostructures at a copolymer crosslinking density (CLD) of 9%. This investigation of chain exchange behaviors in BCP NPs, having architectural and compositional complexity and the ability to moderate chain motion through tailoring the CLD, is expected to be valuable for understanding the dynamic nature of BCP self-assemblies and diversifying the self-assembled structures adopted by these systems. These efforts may guide the rational construction of novel polymer NPs for potential use, for example, as drug delivery platforms and nanoreactors.